Ultrafine NaTi2(PO4)3 Nanoparticles Encapsulated in N-CNFs as Ultra-Stable Electrode for Sodium Storage - Yu, Sicen; Wan, Yi; Shang, Chaoqun; Wang, Zhenyu; Zhou, Liangjun; Zou, Jianli; Cheng, Hua; Lu, Zhouguang (Frontiers in Chemistry, 2018)
We present a feasible method for the preparation of one-dimensional N-doping carbon nanofibers encapsulated NaTi2(PO4)3 (NTP-NCNFs) through electrospinning accompanied by calcination. The poor electrical conductivity of NTP is significantly improved and the as-prepared NTP-NCNFs exhibit stable and ultrafast sodium-storage capability. The NTP-NCNFs maintains a stable specific capacity of 121 mAh g-1 at 10 C after 2000 cycles, which only drop to 105 mAh g-1 after 20000 cycles. Furthermore, the NTP-NCNFs show excellent rate performance from 0.2 C to 20 C, whose recovery efficiency still reaches 99.43%. The superior electrochemical property is mainly attributed to the large specific surface area, high porosity, N-doping carbon coating, and one-dimensional structure of NTP-NCNFs.